2020
DOI: 10.1111/jop.13018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of IL‐6 levels and +3954 polymorphism of IL‐1β in burning mouth syndrome: A systematic review and meta‐analysis

Abstract: This study evaluated IL‐6 salivary levels as well as the +3954 polymorphism of IL‐1β in patients with burning mouth syndrome and healthy individuals, through case‐control studies. This systematic review and meta‐analysis followed the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. We conducted this research in PubMed/MEDLINE, Cochrane Library and Web of Science databases. The risk of bias was measured based in the Newcastle‐Ottawa Scale. Researches with a group of patients with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…This resulted in 33 possible references. After reading the full‐text articles, 16 references were discarded for the following reasons: one for not having a CG (Kang et al, 2017), one for not analyzing biomarkers (Castillo‐Felipe et al, 2021), two for being letters to the editor (Boras et al, 2006; López‐Jornet et al, 2009), four for evaluating genetic polymorphisms (Campello et al, 2020; Guimarães et al, 2006; Kim et al, 2017; Vucićević‐Boras et al, 2003), five for not clarifying the diagnostic criteria used for BMS (Hershkovich & Nagler, 2004; Loeb et al, 2008; Simcić et al, 2006; Srinivasan et al, 2008; Suh et al, 2009), and three for not presenting numerical values for biomarker levels (Acharya et al, 2019; Ji et al, 2017; Kho et al, 2013; these values were requested from the authors, and no response was obtained). Finally, 17 studies were included in this systematic review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This resulted in 33 possible references. After reading the full‐text articles, 16 references were discarded for the following reasons: one for not having a CG (Kang et al, 2017), one for not analyzing biomarkers (Castillo‐Felipe et al, 2021), two for being letters to the editor (Boras et al, 2006; López‐Jornet et al, 2009), four for evaluating genetic polymorphisms (Campello et al, 2020; Guimarães et al, 2006; Kim et al, 2017; Vucićević‐Boras et al, 2003), five for not clarifying the diagnostic criteria used for BMS (Hershkovich & Nagler, 2004; Loeb et al, 2008; Simcić et al, 2006; Srinivasan et al, 2008; Suh et al, 2009), and three for not presenting numerical values for biomarker levels (Acharya et al, 2019; Ji et al, 2017; Kho et al, 2013; these values were requested from the authors, and no response was obtained). Finally, 17 studies were included in this systematic review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…BMS patients suffer bilateral intraoral pain or burning sensation that can vary in intensity without obvious clinical changes. The most frequent location of the pain is the tip of the tongue, but it can also affect palate and lips (Acharya et al, 2019; Campello et al, 2020; Dias Fernandes et al, 2009; Ji et al, 2017; Lopez‐Jornet et al, 2020; Pekiner et al, 2009; Simcić et al, 2006). Pain is often accompanied by xerostomia (without hyposalivation), dysesthesia, and taste alterations (Acharya et al, 2019; Campello et al, 2020; Dias Fernandes et al, 2009; Imura et al, 2016; Ji et al, 2017; Lončar‐Brzak et al, 2020; Pekiner et al, 2009; Simcić et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For some time, there have been indications that BMS affects people with personalities that are susceptible to anxiety and depression [ 6 , 10 , 11 ] more than those who do not experience such issues. It is a complex disease, and several pathophysiological mechanisms have been described that explain the condition [ 12 , 13 ] of which the following are particularly worth mentioning: (i) alteration in dopaminergic transmission at a central level. In fact, the dopaminergic blink reflex is exaggerated in some patients with BMS [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Which could explain the thermal and painful sensitivity in the tongue in these patients, as well as an increase in certain taste detection thresholds [ 17 ]. Some recent studies have suggested that, although not clinically visible, inflammation is the cause of the sensation of pain, with this being linked to cytokine actions [ 13 ]. Other studies have indicated that a genetic variation of the dopamine D2 receptor contributes to the sensation of pain [ 18 ]; nonetheless, mounting evidence has indicated the presence of hormonal, psychosocial, genetic and/or neuropathic causative factors [ 4 ], and, to date, final common consensus is yet to be reached.…”
Section: Introductionmentioning
confidence: 99%